2020
DOI: 10.36351/pjo.v36i2.896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Binocular Vision Problems on Childhood Academic Performance and Teachers' Perspective

Abstract: Purpose:  To see the effect of binocular vision problems on childhood academic performance and to record the teacher's perspectives about childhood eye care in Khartoum State of Sudan. Place and Duration of Study:  A descriptive cross-sectional study done among the school going children in the Khartoum State of Sudan during the year 2018. Study Design:  Descriptive cross sectional study. Material and Methods:  Three hundred and forty (340) primary school children’s were recruited for study by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…12 While low vision among children is less common than adults, it has a serious significant negative impact on the lifespan of the child with an estimate of 60% of children dying within one year of becoming blind. 13 This study revealed that majority 59% of the patients attending low vision clinics were males which was consistent with Uprety, et al 10 They found that 63.7% of patients attending low vision clinics were males. The most common age group affected by the low vision in the current study was 10 to 16 years.…”
Section: Discussionsupporting
confidence: 87%
“…12 While low vision among children is less common than adults, it has a serious significant negative impact on the lifespan of the child with an estimate of 60% of children dying within one year of becoming blind. 13 This study revealed that majority 59% of the patients attending low vision clinics were males which was consistent with Uprety, et al 10 They found that 63.7% of patients attending low vision clinics were males. The most common age group affected by the low vision in the current study was 10 to 16 years.…”
Section: Discussionsupporting
confidence: 87%
“…Of the 22 705 articles initially captured, the study found 29 publications from 10 African countries that met the inclusion criteria ( Fig. 2 ) 12 63 . The studies reviewed mostly reported that the main barriers were non-availability, non-accessibility, and non-affordability of eye care services in addition to paediatric eye care not being a priority agenda in many Africa health systems 6 – 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study found a link between academic performance and children's phoric state. In this sense, Arasheed et al [36] concluded that convergence insufficiency and a weak positive fusional reserve are associated with academic failure. Concurrently, Scheiman et al [37] reported that a significant improvement in reading capabilities was observed after treating convergence insufficiency.…”
Section: Discussionmentioning
confidence: 99%